The Use of the Partner Surveillance Scale in Instagram: Psychometric Evaluation Based on the Graded Response Model - Suryadi, Bambang; Putra, Muhammad Dwirifqi Kharisma (Faculty of Psychology, Universitas Gadjah Mada, 2020)
The use of social media, especially Instagram, has become an increasingly powerful form of daily activity. This social media affects the romantic relationship of people, where people in relationships can conduct surveillance on the behaviors of their partner. This study provides an analysis of the psychometric properties of the Indonesian version of the Partner Surveillance Scale which contains 15 items and used a 4-point Likert scale format. The study recruited 214 female university students aged 17-23 years old, who used Instagram. The Graded Response Model (GRM) method was applied. As a result, the Indonesian version of the Partner Surveillance Scale was proved to have good psychometrics properties and had good fit to the GRM. All assumptions of GRM were met and the scale had high reliability. But, it should be noted that some items did not fit well with the model.Â The results of this study also provide an alternative to the use of Confirmatory Factor Analysis (CFA) in analyzing polytomous data with GRM. This study concluded that the psychometric properties of the Partner Surveillance Scale were good.Â